2018 Computing in Cardiology Conference (CinC) 2018
DOI: 10.22489/cinc.2018.289
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Venous Waveform Signal for Heart Rate Variability Monitoring

Abstract: Heart rate variability (HRV) at rest is widely accepted as a non-invasive measure of autonomic nervous system regulation of the heart. A novel technology has been developed by VoluMetrix®that captures venous waveforms via sensors on the volar aspect of the wrist, called NIVAband. In this study, we aim to assess its validity to determine pulse rate variability as a surrogate of HRV. Seven volunteers were recorded while breathing both spontaneously and at a fixed slow pace. Subjects wore a NIVAband and the ECG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This may be because STT is not as good estimator of respiration as it is PRV in this particular application. The respiratory peak has been obtained from the PRV instead of from the signal PSD, as in [5], because in the NIVA signal the respiration band is heavily filtered, probably due to the high-pass nature of the derivative, and it is difficult to discriminate a peak there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because STT is not as good estimator of respiration as it is PRV in this particular application. The respiratory peak has been obtained from the PRV instead of from the signal PSD, as in [5], because in the NIVA signal the respiration band is heavily filtered, probably due to the high-pass nature of the derivative, and it is difficult to discriminate a peak there.…”
Section: Discussionmentioning
confidence: 99%
“…The development of this device was motivated by some recent results of peripheral intra venous analysis that showed it is a promising indicator in blood volume assessment and hemorrhages [3,4]. The research of Hernando et al [5,6] has demonstrated that NIVA is a reliable surrogate of HRV under resting conditions. In addition, they found a significantly higher power within the High Frequency (HF) band at NIVA, defined as the band centered at the respiratory rate (RR).…”
Section: Introductionmentioning
confidence: 99%
“…They propose Non-Invasive Venous waveform Analysis (NIVA) to obtain information on volume status, heart rate, and respiratory rate. In a previous work, we validated the ability of NIVAband to provide a measure of autonomic nervous system (ANS) via pulse rate variability (PRV) analysis [3]. Results showed that high frequency power was significantly higher in PRV analysis from NIVA than in heart rate variability (HRV) from ECG, suggesting that the NIVA signal may enhance measurement of parasympathetic activity.…”
Section: Introductionmentioning
confidence: 89%
“… 1 , 2 , 6 , 7 Furthermore, a piezoelectric sensor placed on the volar aspect of the wrist, directly over the superficial veins, has also allowed for non-invasive capture of the peripheral venous waveform. 3 , 4 , 16 , 17 The piezoelectric sensor is connected to a control box that amplifies the venous waveform detected from vibrations related to the low amplitude pulsatile flow of venous blood. In addition to direct invasive and non-invasive capture of peripheral venous waveforms, indirect analysis of plethysmographic waveforms have been used to detect the peripheral venous waveform.…”
Section: Methods Of Venous Waveform Acquisitionmentioning
confidence: 99%
“…[1][2][3][4]6,7,16,17 These algorithms are referred to as Peripheral IntraVenous waveform Analysis (PIVA) in directly transduced waveforms 1,2,6,7 and NonInvasive Venous waveform Analysis (NIVA) in waveforms obtained non-invasively with a piezoelectric sensor placed on the wrist. 3,4,16,17 A number of other algorithms in the frequency domain have been developed and tested, including calculation of overall signal power or tracking changes in the amplitude of the fundamental pulse frequency across intravascular volume events. 1,2,5,6 Clinical applications of venous waveforms One of the largest clinical applications of volume status assessment is the detection of hemorrhage, which is traditionally difficult to identify clinically.…”
Section: Techniques For Waveform Analysismentioning
confidence: 99%